Motivasi Belajar Santri Dalam Penguasaan Kaidah Daqu Di Pesantren Tahfizh Daarul Qur’an Tegineneng Pesawaran - Akbar Rahman; Agus Pahrudin; Nanang Supriadi; Ali Murtadho (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This research is motivated by the anomaly problem of the speed gap of students in mastering the Daqu Rules method, even though they study in the ecosystem and use the same curriculum. This duration inequality is strongly indicated to be disrupted by a psychological determinant variable, namely learning motivation. Therefore, this study aims to investigate and analyze the dynamics of students' learning motivation in mastering the Daqu Rules at the Tahfizh Daarul Qur'an Islamic Boarding School Tegineneng Pesawaran. The research applied a qualitative method of case study design using purposive sampling on fast, medium, and slow student groups, and collected holistic data through observation, interview, and documentation study techniques. The findings of the research prove that students who are dominated by intrinsic motivations such as theological awareness and independent goals show very rigid discipline, proactive participation, and much faster learning acceleration. On the other hand, students who are extrinsically motivated because of the demands of their parents or simply the rules of the pesantren are prone to experiencing sporadic demotivation, boredom, and stagnation in completing material up to more than one semester. As a concrete recommendation, educators (asatidz) are required to carry out systemic reorientation by not only acting as mechanical pedagogical instructors, but are obliged to transform into emotional architects who proactively engineer a supportive environment to maintain the intrinsic motivation of students.